The effects of audio feedback on the L2 writing quality of Egyptian university students - Abouelazm, Omar (AUC Knowledge Fountain, 2014)
The present study investigates the effects of training ESL students to utilize audio feedback on the fluency, accuracy, content and organization of their writing. It also examines ESL student attitudes and perceptions towards audio feedback and audio feedback training. Audio feedback is an innovative error correction technique in which the teacher records comments on students’ writing and saves them as an audio file. The audio file is then used by the student to revise a piece of writing. Audio feedback training refers to the idea of training ESL students on how to successfully utilize audio feedback in order to reap its benefits during writing revision. Using a pretest and posttest utilizing TOFEL argumentative prompts, the researcher collected writing samples from 39 ESL students studying English at an American accredited university in Cairo, Egypt. The participants were divided into two groups, a control group and an experimental group. Prior to the posttest, both groups were given audio feedback on writing errors pertaining to fluency, accuracy, content, and organization. The experimental group also received a 20-minute audio feedback training session. After the posttest, both groups were given semi-structured questionnaires eliciting attitudes and perceptions of audio feedback. The experimental group was given extra items on the questionnaire that elicited attitudes and perceptions of audio feedback training. T-tests were run to determine if any significant differences existed between the two groups. Findings reported no significant differences between the two groups with respect to changes in mean scores from pretest to posttest. However, the experimental group showed significant positive differences in the scores for accuracy and content from pretest to posttest. Questionnaire results indicated that participants had an overall positive reaction to audio feedback. Participants in the experimental group reacted positively towards audio feedback training and indicated that it was necessary in order to benefit from audio feedback. Results suggest that audio feedback training may have been the reason behind the gains observed by the v experimental group. The researcher suggests further research be conducted on the effects of audio feedback on writing quality as well as training in feedback.